1969
DOI: 10.1139/o69-140
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate kinase: modulation by L-phenylalanine and L-alanine

Abstract: L-Phenylalanine was found to be a competitive inhibitor of pyruvate kinase in the rat prostate, seminal vesicles, uterus, and skeletal muscle. In contrast, L-alanine exerted no appreciable effect on pyruvate kinase activity but was capable of protecting against, as well as reversing, the inhibition produced by L-phenylalanine. The results suggest that the interactions between L-phenylalanine and L-alanine are important to the regulation of pyruvate kinase activity in tissues containing the M-type isozyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…10. Similar results were obtained for SGPK-I and SGPK-II and are in agreement with other reports on rabbit muscle (Carminatti et al, 1971) and rat tissues (Vijayvargiya et al, 1969).…”
Section: Alaninesupporting
confidence: 93%
See 1 more Smart Citation
“…10. Similar results were obtained for SGPK-I and SGPK-II and are in agreement with other reports on rabbit muscle (Carminatti et al, 1971) and rat tissues (Vijayvargiya et al, 1969).…”
Section: Alaninesupporting
confidence: 93%
“…Vijayvargiya et al (1969) and Carminatti et al (1971) reported that L-phenylalanine inhibits the pyruvate kinase (M type) by competing with the substrate, PEP. As shown in Fig.…”
Section: « • • •mentioning
confidence: 99%
“…On the other hand, there is no kinetic evidence so far, suggesting that the enzyme from muscle, which has been extensively investigated [2], might have allosteric properties. Recently it was reported that type M pyruvate kinase from skeletal muscle [3] and other tissues [3,4] is inhibited by phenylalanine in a competitive way. It was also found that L-alanine can reverse this inhibition [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was reported that type M pyruvate kinase from skeletal muscle [3] and other tissues [3,4] is inhibited by phenylalanine in a competitive way. It was also found that L-alanine can reverse this inhibition [3].…”
Section: Introductionmentioning
confidence: 99%
“…Phenylpyruvate has been shown to inhibit a number of brain enzymes (Patel, 1972;Land & Clark, 1973) and phenylalanine inhibits pyruvate kinase from brain (Weber, 1969) and other tissues (Vijayvargiya, Schwark & Singhal, 1969). In the present study, pyruvate kinase and citrate synthetase in rabbit lymphocytes were studied.…”
Section: Discussionmentioning
confidence: 88%